Alachlor removal over Fe-TiO2 loaded on granular activated carbon support under UV and visible light irradiation - Rivera, Kim Katrina P. (College of Engineering, University of the Philippines Diliman, 2014)
Alachlor is a recalcitrant carcinogenic contaminant that may easily spread in water source due to its wide usage as an herbicide. The aim of this study is to synthesize Fe-TiO2 on granular activated carbon (GAC) support via hydrothermal method for the photodegradation of alachlor under ultraviolet and visible light irradiation. The effects of Fe-TiO2 loading, initial alachlor concentration, and initial solution pH were determined using Box-Behnken Design (BBD). X-ray diffraction (XRD) analysis of Fe-TiO2-GAC samples showed anatase TiO2 peaks as well as the graphite peak from carbon. Scanning electron microscope (SEM) images verified that Fe-TiO2 was immobilized onto the GAC. In UV photocatalysis, the interaction between Fe-TiO2 loading and initial alachlor concentration is significant wherein low Fe-TiO2 loading and 50 ppm initial alachlor concentration increased the removal efficiency. In visible light photocatalysis low Fe-TiO2 loading and initial alachlor concentrations of 30 and 70 ppm are significant. The interactions of the initial solution pH with Fe-TiO2 loading and initial alachlor concentration are also significant in which low solution pH increased alachlor removal for low Fe-TiO2 loading and low initial concentration. The highest alachlor removal percentages obtained were 99.74% and 99.96% under UV and visible light irradiation, respectively.